2021
DOI: 10.1021/acsnano.0c04489
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein B Promotes Cytosolic SiRNA Delivery by Adopting a Virus-like Mechanism of Action

Abstract: RNA therapeutics are poised to revolutionize medicine. To unlock the full potential of RNA drugs, safe and efficient (nano)formulations to deliver them inside target cells are required. Endosomal sequestration of nanocarriers represents a major bottleneck in nucleic acid delivery. Gaining more detailed information on the intracellular behavior of RNA nanocarriers is crucial to rationally develop delivery systems with improved therapeutic efficiency. Surfactant protein B (SP-B) is a key component of pulmonary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…They are capable of entering cells and may be released in cytoplasm, which is visible in the TEM images. This is interesting in view of recent findings about cytosolic delivery of RNA under a virus-like mechanism . It is also clear that free structural RNA can be processed in cells by Dicer endonuclease, which leads to gene regulation via RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…They are capable of entering cells and may be released in cytoplasm, which is visible in the TEM images. This is interesting in view of recent findings about cytosolic delivery of RNA under a virus-like mechanism . It is also clear that free structural RNA can be processed in cells by Dicer endonuclease, which leads to gene regulation via RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular uptake and endosome escape results showed that most siRNA could escape from the lysosomes and be transported to the cytosol, which suggested that the mechanism may involve the perturbation of intracellular phospholipid membranes. [ 30 ] Further studies need to be performed to gain better understanding.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the latter enabled to investigate the impact of the lipid components on the delivery-promoting activity of SP-B in more detail. In vitro studies demonstrated the importance of a fluid lipid bilayer to support SP-B, with cholesterol not exceeding physiological levels, while the type of anionic lipid was less critical [ 50 ].…”
Section: Pulmonary Surfactant In the Fight Against Covid-19mentioning
confidence: 99%
“…Unfortunately, current state-of-the-art siRNA nanomedicines have difficulties in overcoming the many extra- and intracellular barriers upon topical administration to the lung, leading to inefficient cytosolic delivery [ 43 , 44 ]. In this regard, it was recently disclosed by Raemdonck and co -workers that exogenous PS has the unexpected property of promoting cytosolic siRNA delivery by polymeric nanomedicines [ [45] , [46] , [47] , [48] , [49] , [50] ]. As such, exogenous PS can be regarded as a multifaceted biomaterial, enabling both direct treatment of COVID-19-related lung dysfunction as well as improved pulmonary delivery of small molecular- and macromolecular drugs.…”
Section: Introductionmentioning
confidence: 99%